A Review of the Pharmacological and Nutraceutical Properties of Cynodon dactylon - Shweta Das; Sonia Morya; Arno Neumann; Vijay Kumar Chattu (Pharmacognosy Research, 2021)
Background: Cynodon dactylon is the scientific name of the common perennial grass whose lustre of green pasture covers the land. In layman’s language, it is seen as a surface pasture in a sports field, garden lawns or terrace gardens, or as an unwanted weed in gardens. Many are unaware of its phytoconstituents, pharmacological and nutraceutical properties which progressively make science to aim for C. dactylon’s enormous nutraceutical potential in curing problems like ulcers, diabetes, arrhythmia, diarrhoea, inflammation, edema and etc. Objectives: To discuss the constituents of phytochemicals and nutraceutical properties of C. dactylon with its curative investigation for various common ailments. Materials and Methods: Different kinds of extracts i.e. aqueous extract, ethanolic extract, alcoholic extract, hydro-alcoholic extracts etc. of C. dactylon were taken into account to study their curing potential against ailments organically. Results: Having its origin from east of Africa, it contains large amounts of biologically active compounds or phytochemical compounds, which has attracted many researchers to study its curative nutraceutical properties. Experiments conducted on animals have resulted in the effect of C. dactylon is, in the field of whether treating ailments or healing up excision or incision wounds, reducing ulcers, or improving the functioning of the muscular system and the circulatory system of the body. Conclusion: Biologically active phytocontituents in C. dactylon effective against the bodily ailments and are of high importance once the products are made easily available.
Keywords: Cynodon dactylon; Extracts; Nutraceutical; Pharmacological; Phytoconstituents